Analytical loss calculation models of a choke-based filter - Al-Zubeidi, Ramy (My University, 2024)
The purpose of this thesis is to examine the loss calculation of the foil winding choke and to develop an analytical calculation model to support the design of the main circuit. The analytical calculation model should be easy to use, accurate, reliable and flexible. The analytical calculation model should calculate the winding and core losses of the choke. The tool must be able to determine the choke losses at different load points when the output frequency and modulation index vary. Two analytical calculation models were developed to support the main circuit design. The operation of the calculation models is based on the baseline values entered by the user, which are used in the calculation models to determine the winding and core losses that are important to the choke. The first analytical calculation model calculates only core and winding losses. In addition to this, a separate analytical calculation model to determine AC winding losses was developed to support FEMM-2D simulation software. The purpose of the simulation model is to supplement the calculation tool to determine the exact loss result. During this thesis, some simulations and calculations were performed. The core simulations were used to investigate, among other things, the effect of the air gap. Primarily, it was examined how the fringing flux behaves when the number and length of air gaps increase. Winding simulations were performed to study, among other things, winding losses. In addition to this, the winding at the air gaps was examined, as well as the effect of the core shape on the magnitude of the flux density and total losses. Simulations and calculations were also performed to obtain more information about skin and proximity effects. As a result of the work, the necessary analytical calculation models were developed in the MATLAB environment. Regarding DC winding losses, the relative error between the analytical calculation model and the simulation result was 13 %, which indicates that the results corresponded well to each other. Similarly, for AC winding losses, the relative error between the analytical calculation model and the simulation result was 27 %. This difference can be explained by the incomplete calculation of winding resistance in a simulation environment since the exact calculation of the winding resistance can only be done using the defined equations. Core losses were modeled using Steinmetz equation. According to the analytical calculation model, maximum losses in the frequency range from 50 Hz to 20 kHz occur at 4 kHz.

Tämän lopputyön tarkoituksena on tarkastella foliokäämisen kuristimen häviölaskentaa ja kehittää pääpiirin suunnittelun tueksi analyyttinen laskentamalli. Analyyttisen laskentamallin tulee olla helppokäyttöinen, tarkka, luotettava ja joustava. Analyyttisestä laskentamallista tulee selvitä kuristimen käämitys- ja rautaydinhäviöt. Työkalun tulee pystyä määrittämään kuristinhäviöt eri kuormituspisteissä, kun lähtötaajuus ja modulaatioindeksi vaihtelevat. Pääpiirin suunnittelun tueksi kehitettiin kaksi analyyttistä laskentamallia. Laskentamallien toiminta perustuu käyttäjän syöttämiin lähtöarvoihin, joiden perusteella laskentamallit määrittävät kuristimelle tärkeimmät käämi- ja sydänhäviöt. Ensimmäinen analyyttinen laskentamalli laskee kuristimen rautasydämen ja käämityksen häviöt. Tämän lisäksi FEMM-2D -simulointiohjelmiston tueksi kehitettiin erillinen analyyttinen laskentamalli AC-käämityshäviöiden määrittämiseksi. Simulointimallin tarkoituksena on täydentää laskentatyökalua tarkan häviötuloksen määrittämiseksi. Työn aikana suoritettiin joitakin simulointeja ja mittauksia. Rautaytimelle tehtyjen simulointien avulla haluttiin selvittää muun muassa ilmaraon vaikutusta. Lähtökohtaisesti selvitettiin, miten hajavuo käyttäytyy, kun ilma-aukkojen määrä ja pituus kasvavat. Käämitykselle tehtyjen simulointien avulla selvitettiin muun muassa muodostuneet käämihäviöt. Tämän lisäksi selvitettiin käämitystä ilma-aukkojen kohdalla ja sydämen muodon vaikutusta vuontiheyden suuruuteen ja kokonaishäviöihin. Simulointien ja mittausten avulla haluttiin saada myös lisätietoa virranahto- ja lähivaikutusilmiöistä. Työn tuloksena saatiin kehitettyä tarvittavat analyyttiset laskentamallit, jotka molemmat luotiin MATLAB-ympäristöön. DC-käämityshäviöiden osalta analyyttisen laskentamallin ja simulointituloksen virhemarginaali oli 13 %, mikä osoittaa, että tulokset vastasivat hyvin toisiaan. Vastaavasti AC-käämityshäviöiden osalta analyyttisen laskentamallin ja simulointituloksen virhemarginaali oli 27 %. Tätä eroa voidaan selittää simuloinnin puutteellisella laskennalla, koska käämiresistanssin tarkka laskenta onnistuu vain määriteltyjen yhtälöiden avulla. Sydänhäviöt mallinnettiin Steinmetzin yhtälön avulla. Analyyttisen laskentamallin mukaan suurimmat häviöt taajuusalueella 50 Hz ‒ 20 kHz syntyvät 4 kHz kohdalla.
Keywords: simulointi; suodattimet; laskentamallit; fi=Sähkötekniikka|en=Electrical Engineering|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|